(untitled) (Al-Academy, 2015)
Addressed the problem of the research is marked: (Performing processors for the time between Impressionism and superrealism) the concept of time and how to submit artwork. The search came in four sections: general framework for research and identified the research problem and the need for him. With an indication of the importance of his presence. Then determine the research objectives of (detection processors performing to the concept of time in works of art in each of Impressionism and superrealism. And a comparison between them to reveal similarities and differences), followed by the establishment of boundaries Find three (objectivity, the temporal and spatial) were then determine the terms related to the title. Then provide the theoretical framework and indicators that resulted from academic theorizing of the subject. The researcher has identified three addresses implied within this framework to ensure reading placed search according to the various frameworks tariff. Were as follows: the concept of Performance. Performance in school Impressionism. Performance in motion superrealism. The third chapter was devoted to the search procedures, through thoughtful society and revealed the selected sample of it (4 boards) and then specify the search tool and determine the methodology, followed by an analysis of the sample. The fourth chapter included the search results, including:1. Impressionism was supposed high-resolution camera before its existence, this curriculum was adopted in technical work, while actually that superrealism benefited from its existence.2. Impressionism stop time and assume that appropriate selection flesh artist to documented, while The superrealism has stopped and select by artist to their appropriate moments, via the camera. What a dream by Impressionist artist, achieved artist superrealism, with the help of technology.3. Impressionist artist predicted the existence of details to Leave the eye, represents an intuitive manner, while the artist Alsobriala sensory seen through technical given that proved its existence.4. Impressionism is a performance act of imagination woven into the details of the decree scene. And Alsobrialah performance monitoring precise optical tubeless to the mental effort of the Impressionists